The European Parliament and Supranational Party System : a study in institutional development - Kreppel, Amie, 1968- (Cambridge studies in comparative politics., 2001)
"This book examines the impact of increased legislative power and political authority on the internal development of the European Parliament and the supranational party group system. This is done through an analysis of changes in the hierarchical structures that regulate the internal organization of both the EP as a whole and the individual party groups. In addition, the changing pattern of coalition formation between party groups across time and legislative procedure is analyzed. The trends of internal development examined suggest that the increases in EP power that have occurred since the creation of the cooperation procedure by the Single European Act in 1987 have caused a fundamental shift in the character of the European Parliament as a legislative institution.